Influence of Duct Configurations on the Performance of Solar-Assisted Heat Pump Dryer for Drying Tobacco Leaves - Salum Abdulkarim Suleiman; Alexander Pogrebnoi; Thomas T. Kivevele (International Journal of Photoenergy)
In the present study, a solar-assisted heat pump dryer (SAHPD) has been designed, fabricated, and tested its performance on drying tobacco leaves. The hot air generated from the solar collector and condenser unit of the heat pump was used as a source of heat in the drying chamber. In this study, we investigated the influence of three duct configurations (open, partially closed, and completely closed) on the thermal performance of SAHPD to establish the best configuration for drying tobacco leaves. The average drying temperature was found to be 66, 64, and 60°C; the coefficient of performance of the heat pump was 3.4, 3.2, and 3.0; the heat energy contribution from the solar collector was 6.6%, 5.0%, and 5.1% while for the condenser was 93.4%, 95.0%, and 94.9%, and electrical energy consumption was 2.3, 2.8, and 2.6 kWh, for the open, partially closed, and completely closed duct system, respectively. Based on these results, the open system demonstrated the best performance. According to the study’s findings, SAHPD has been shown to be an energy-efficient method of drying tobacco leaves and is environmentally friendly as opposed to the conventional use of wood fuel, which results in environmental pollution, desertification, and deforestation.